Flexible and lightweight microcellular RGO@Pebax composites with synergistic 3D conductive channels and microcracks for piezoresistive sensors. (August 2019) - Dong, Diandian; Ma, Jianzhong; Ma, Zhonglei; Chen, Yongmei; Zhang, Hongming; Shao, Liang; Gao, Jinpeng; Wei, Linfeng; Wei, Ajing; Kang, Songlei
Abstract: Piezoresistive sensors with high flexibility, lightweight and high sensitivity are crucial in variable conductors and wearable devices. Herein, microcellular poly(ether-block-amide) beads coated with reduced graphene oxide (RGO@Pebax) composites with synergistic 3D conductive channels and microcracks were fabricated via the supercritical CO2 foaming followed by dip-coating hydrogen bond assembly, compression moulding and in-situ reduction. The microcellular RGO@Pebax composites exhibit high flexibility (up to 50% compressibility) and low mass density (down to 0.2 g/cm 3 ) due to the incorporation of microcellular structures and 3D interconnected channels. The resultant microcellular RGO@Pebax composites-based piezoresistive sensors exhibit excellent sensing capacity due to the synergistic effect of double mechanisms: "disconnect-connect" transition of microcracks and increased contact area in the 3D conductive channels. Moreover, the piezoresistive sensors exhibit outstanding reliability and stability during the long-term repeated compression strain. Functional applications of the piezoresistive sensors have been demonstrated, indicating their excellent application potentials in variable conductors and wearable devices.